Análisis a los Estados Financieros de la Procesadora de Alimentos Maquinbal C Ltda, de la Ciudad de Balsas 2020-2021 - Apolo Valle, Geraldyn Jamileth (2023)
The Curricular Integration Work entitled: "Analysis of the Financial Statements of “Procesadora de Alimentos Maquinbal C Ltda,” of the City of Balsas, Period 2020-2021" fulfills the general objective of carrying out the financial analysis to know and analyze the truthful economic and financial situation. To comply with the first specific objective, we developed a vertical and horizontal analysis, where the highest concentration is in its Non-Current Assets, with 85.10% in 2020 and 72.42% in 2021; Current Assets represented 14.90% in 2020 and 27.58% in 2021; Liabilities reflect 90.39% in 2020 and 80.89% in 2021, values that correspond to the partners financing the company; in the economic structure, sales represent 100% in both periods, and the Cost of Sales in 2020 corresponds to 78.22% and 86.26% in 2021. Next, we applied the horizontal analysis to the financial statements for the periods 2020-2021 to determine the variations that reflect each of the accounts that make up the financial statements, where the Assets had a growth of 37.3%; concerning its Liabilities, these increased by 3.8%; the Equity increased by 130.6%; in its economic structure, Income increased by 96.09%, a value that reflects that in 2021 sales had a greater incidence; likewise, Costs had an increase of 116.26%; Expenses had a decrease of -13.01%, and finally, the Results for the fiscal year had a positive variation equivalent to 42.41%, which is a very satisfactory result for the company. Then in the second objective, we determined the calculation of financial indicators regarding the Liquidity indicator. Its Current Ratio corresponds to the measurement between Current Assets over Current Financial Liabilities, where we obtained 0.16 in the year 2020, while in 2021, the 0.40 values that highlight that the company in both periods does not have liquidity. The Indebtedness of Assets indicator highlighted that; since the company receives financing from third parties and has a high level of risk caused by the debts contracted in the short term. Finally, we prepared a financial report, which consists of detailing the relevant information from the application of the vertical and horizontal analysis and from the economic indicators to allow the company to analyze its situation and make timely decisions, so we recommended performing a thorough financial analysis of Maquinbal Company at the end of each financial period